High isolation of mm-wave T-R switch design using open loop square ring DGS - Othman, A.; Majid, H.A.; Al-Fadhali, N.; Shairi, Noor Azwan; Zolkefli, Amirul Aizat; Abidin, Z.Z.; Mohd Ibrahim, Imran; Zakaria, Zahriladha (2023)
This research studies the use of a switchable open loop square ring defected ground structure (DGS) to provide high isolation in a discrete transmit-receive (T-R) millimeter-wave (mm-wave) RF switch operating in the 26 GHz band for a 5G application. The simulation demonstrated that the switchable DGS had aided the T-R switch in generating a large isolation performance of more than 30 dB in the 26 GHz band.